Selflessness is sexy: reported helping behaviour increases desirability of men and women as long-term sexual partners - Moore, David; Wigby, Stuart; English, Sinead; Wong, Sonny; Székely, Tamás; Harrison, Freya (BioMed Central, 2013)
Background Despite its short-term costs, behaviour that appears altruistic can increase an individual’s inclusive fitness by earning direct (selfish) and/or indirect (kin-selected) benefits. An evolved preference for other-regarding or helping behaviour in potential mates has been proposed as an additional mechanism by which these behaviours can yield direct fitness benefits in humans. Results We asked 32 heterosexual women and 35 heterosexual men to rate the attractiveness of members of the opposite sex in the presence and the absence of information about helping behaviours. Reports of helping behaviour were associated with a significant increase in the attractiveness of both men and women as potential long-term sexual partners. Altruism also increased the attractiveness of men as potential partners for short-term flings, but to a lesser extent than when the same men were being considered for long-term relationships. Altruism did not affect the attractiveness of women as partners for short-term flings. Conclusions Our results unite two important areas of evolutionary theory – social evolution and sexual selection – and extend the list of means by which helping behaviours, which appear at first glance to be costly to the actor, can in fact earn direct fitness benefits. Helping behaviours may be attractive because they signal ‘good genes’ and/or because they are perceived as a signal of likely provision of non-genetic benefits (e.g. parental care). Exactly why helping behaviours in a non-mating context might be attractive to potential mates, and whether they are honest signals of mate quality, remains to be elucidated